Pengaruh Growth Opportunity, Struktur Aktiva, dan Board Diversity Terhadap Nilai Perusahaan dengan Risk Committee Sebagai Variabel Moderasi - Rosia, Rina (UIN MAHMUD YUNUS BATUSANGKAR, 2024)
This study aims to analyze the effect of growth opportunity, asset structure, and board diversity on firm value with the risk committee as a moderating variable. Growth opportunity is proxied by the Price Earning Ratio (PER), asset structure is calculated by a comparison between fixed assets and total assets, and board diversity is proxied by the gender of the board of directors, the age of the board of directors, and the educational background of the board of directors. Firm value is proxied by the Tobin's Q ratio, and risk committee is measured by a dummy variable. This type of research is quantitative research with a population of manufacturing companies registered at ISSI for the 2019-2021 period and a total sample of 69 samples from 23 company data obtained through the purposive sampling method. Methods of data analysis using panel data regression technique with SPSS software version 25. The result is growth opportunity and the age of the board of directors has a significant positive effect on firm value, while asset structure, gender of the board of directors, and educational background have no effect on firm value. The RMC variable is only able to moderate the effect of growth opportunity on firm value. Meanwhile, RMC was unable to moderate the effect of asset structure, gender of the board of directors, age of the board of directors, and educational background of the board of directors on firm value.